Modelling nitrogen dynamics of a constructed wetland: Nutrient removal process with variable yield - Kornkanok Bunwong (2018)
A three-dimensional system of ordinary differential equations is constructed in order to describe the total nitrogen dynamics of a constructed wetland. With the conditions that the growth rate and the biomass conversion are represented as the Monod or the Michaelis-Menten function and the linear yield function, respectively, the existence of steady states, their linear stability and the existence of local Hopf bifurcation are then investigated. Parameter space classification is then carried out by making use of the various conditions, derived through the stability analysis, which delineate the parameter space into regions of different dynamical behavior. Numerical simulations are then carried out in support of the theoretical results. © 2009 Elsevier Ltd. All rights reserved.